Community Based Tourism: A Global South Perspective - Claudio Milano; Jordi Gascón (Tourism & Management Studies)
The analysis of the impact of Community Based Tourism (CBT) has revealed a significant divergence in assessments. This paper aims to analyse the factors contributing to the observed "Duality Dilemma" in CBT projects. The research seeks to leave behind a simplistic binary perspective that categorises CBT solely as either beneficial or problematic. The paper identifies three key variables contributing to this dual perspective: a) the Context Variable, which displays how the outcomes of CBT projects m can vary based on the specific circumstances in which they are implemented; b) the Methodological Variable, which underlines the importance of developing long-term and longitudinal fieldwork to avoid a biased analysis based on the short-term observations; c) the Paradigm Variable which takes into account that the researcher's theoretical framework inevitably shapes their focus, potentially emphasising certain outcomes over others. Finally, the paper draws on empirical evidence based on a 30-year longitudinal ethnographic study conducted on Amantaní island (Lake Titicaca, Peruvian Andes).